Analysis Of Telkom's Strategy And Business Model Fixed Broadband To Achieve Sustainable Competitive Growth - Yuni Praticia Simarmata; Abd. Rakhman Laba; Andi Ratna Sari Dewi (SEIKO : Journal of Management & Business, 2023)
This study aims to understand the resource potential of doing Telkom's fixed broadband business, understand the environmental influences on Telkom's fixed broadband business, and determine the strategy and business model of Telkom's fixed broadband to achieve sustainable, competitive growth. This study used a descriptive analysis method with a case study strategy that combines the dominant qualitative approach (interviews, focus group discussions, and literature) and accompanied by quantitative data (questionnaire). The objects of research are Speedy existing customers in the cluster housing Griya Inti, Sunter, North Jakarta, to get feedback on the experience of existing fixed broadband services, and Broadband Division management as strategies and business models designers of fixed broadband services in Telkom Indonesia. The results of the analysis of internal and external evaluation matrix show that appropriate strategies for Telkom's fixed broadband business now are hold and maintain. While the results of the interviews and focus group discussions show that in order to achieve a sustainable competitive advantage in the fixed broadband business, the best service experience is very important. This conclusion is also consistent with the results of the analysis of the questionnaire related to Telkom's existing customer experience stating that the customer still feels less than getting a satisfactory service experience in using Telkom's fixed broadband products, while they are willing to pay more if Telkom is able to offer fixed broadband products of a higher quality and may ensure the best experience to the customer. Keywords: Sustainable Competitive Advantage, SWOT Analysis, fixed broadband.